Output Fluctuations in Latin America : What Explains the Recent Slowdown? - Herrera, Santiago (World Bank, Washington, DC, 2014)
The authors explain Latin America's growth slowdown in 1998-1999. To do so, they use two complementary methodologies. The first aims at determining how much of the slowdown can be explained by specific external factors: the terms of trade, international interest rates, spreads on external debt, capital flows, and climatological factors (El Nino). Using quarterly GDP data for the eight largest countries in the region, the authors estimate a dynamic panel showing that 50-60 percent of the slowdown was due to these external factors. The second approach allows for effects on output by some endogeneous variables, such as domestic real interest rates, and real exchange rates. Using monthly industrial performance data, the authors estimate country-specific generalized vector auto-regressions (GVAR) for the largest countries. They find that during the sample period (1992-98) output volatility is mostly associated with shocks to domestic factors, but the slowdown in the sub-period 1998-99 is explained more than 60 percent by shocks to the external factors.